Music sight-reading expertise, visually disrupted score and eye movements - Patricia Arthur; Diana Blom; Sieu Khuu (Journal of Eye Movement Research)
Previous studies have shown that performance at a defined level of music sight reading for pianists (6th Grade) is predictive of eye movement patterns (Waters, 1998) and that such patterns resemble those of text reading experts (Furneaux & Land, 1999; Sloboda, 1974; Truitt, 1997; Wolf, 1976). However, little is known about how expertise might affect eye movement patterns when the score has been visually disrupted using notational features that are unexpected or outside conventional presentation.